2019
DOI: 10.3390/ijerph16183252
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Internet Use with Wellbeing, Mental Health and Health Behaviours of Persons with Disabilities

Abstract: Introduction: There is strong evidence that people with disabilities suffer from a significant digital divide. However, there are reports indicating that Internet use may result in many benefits for those with disabilities. The aim of the study was to assess the impact that the use of the Internet has on the wellbeing and health behaviours of persons with disabilities. Methods: An analysis was carried out using the dataset obtained from Social Diagnosis, a panel study undertaken on a nationally representative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 50 publications
4
20
0
1
Order By: Relevance
“…This result has been confirmed in other studies [10][11][12][13][14][15][16][17][18][19]. Similarly, lower depression levels [5,[20][21][22], better functional capacity [14], better well-being and quality of life [23][24][25], healthier lifestyles [23,26], fewer chronic medical conditions [5], and more favorable cardiovascular risk factors [27] have been associated with a higher likelihood of DIT use in older adults. In contrast, some studies have found no independent association between health status and internet use [4,13].…”
Section: Introductionsupporting
confidence: 73%
“…This result has been confirmed in other studies [10][11][12][13][14][15][16][17][18][19]. Similarly, lower depression levels [5,[20][21][22], better functional capacity [14], better well-being and quality of life [23][24][25], healthier lifestyles [23,26], fewer chronic medical conditions [5], and more favorable cardiovascular risk factors [27] have been associated with a higher likelihood of DIT use in older adults. In contrast, some studies have found no independent association between health status and internet use [4,13].…”
Section: Introductionsupporting
confidence: 73%
“…Therefore, it is not surprising that in the reported study, older adults and elderly persons with disabilities used the Internet less frequently than those without disabilities. However, for persons with disabilities, the use of the Internet may be associated with improved wellbeing and health-related measures, as has been reported earlier [ 71 ].…”
Section: Discussionmentioning
confidence: 59%
“…Studies have also focused on the mental health of the population. For example, the Duplaga study revealed that Internet use was effective in improving adults’ well-being, promoting their mental health, and increasing more beneficial health behaviors [ 19 ]. Fu reported a more significant correlation between social media use and mental health than physical health in older adults [ 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%